Toxic epidermal necrolysis caused by phenobarbital: a case report and literature review - Cheng, Jie; Li, Hui; Li, Yan; Li, Xiao; Wang, Jianjun; Huang, Xin; Cui, XueYan (Frontiers in Pharmacology, 2024)
Background: Toxic epidermal necrolysis (TEN) and Stevens–Johnson syndrome (SJS) are rare, life-threatening immunologic reactions. Previous relevant literature has provided limited information regarding this disease's genetic susceptibility and management principles. Objectives: This study aimed to describe a phenobarbital-induced TEN case report with HLA-B*15:02 and HLA-B*58:01 negative, CYP2C19*1/*2. In addition, we revised the existing literature on phenobarbital-induced SJS/TEN to explore its clinical characteristics. Methods: We describe a woman undergoing treatment with Phenobarbital for status epilepticus who developed classic cutaneous findings of TEN. A systematic search was conducted in the PubMed, Medline, WanFang, and CNKI databases from 1995 to 2023. The search terms used were “Stevens-Johnson Syndrome,” “Toxic Epidermal Necrolysis,” and “Phenobarbital.” Results: We report a case of TEN resulting from phenobarbital; it tested negative for the HLA-B*15:02 and HLA-B*58:01 allele and CYP2C19*1/*2 intermediate metabolism. Supportive treatment with steroids and antihistamines resulted in complete resolution of the skin lesions and improvement in clinical symptoms after 14 days. Physicians and clinical pharmacists should be aware of these potential phenobarbital-related adverse events and closely monitor patients with first-time use of phenobarbital. Among 19 cases were identified in the literature, with 11 (57.9%) cases of SJS, 6 (31.6%) cases of TEN, and 2 (7.2%) cases of SJS-TEN/DRESS overlap. A total of 5 (26.3%) did not survive, of which 4 (21.1%) were under 12 years old and 1 (5.3%) was over 12 years old. Conclusion: Phenobarbital-induced SJS/TEN may still occur in patients who test negative for HLA-B*15:02 and HLA-B*58:01, CYP2C19*1/*2. Most cutaneous adverse events occur early in the course of Phenobarbital therapy and should be closely monitored early in the course of treatment. In addition, PB should be used with caution in patients with a history of asthma and allergy to antipyretics and analgesics.